Biochemical Analysis Tools Methods for Bio-Molecules Studies - Boldura, Oana-Maria; Baltă, Cornel; Sayed Awwad, Nasser (IntechOpen, 2020)
This book explores the role of nucleic acid analysis and the advances it has led to in the field of life sciences. The first section is a collection of chapters covering experimental methods used in molecular biology, the techniques adjacent to these methods, and the steps of analysis before and after obtaining raw DNA data. The second section deals with the principles of chromatography, method development, sample preparation, and industrial applications.